Investigating Childrens Spiritual Experiences through the Health and Physical Education (HPE) Learning Area in Australian Schools - Lynch, Timothy (Journal of religion and health, 2015)
The purpose of this study is to explore spirituality within the Health and Physical Education (HPE) learning area, through investigating childrens experiences within three Brisbane Catholic Education primary schools (Queensland, Australia). There are seven dimensions of wellness: physical, intellectual, emotional, social, spiritual, environmental, and occupational, which are all strongly connected (Robbins et al. in A wellness way of life, 9th edition, McGraw Hill, USA, 2011). It is logical that HPE, which promotes students to adopt lifelong health and well-being, offers opportunities for spirituality to be experienced and warrants investigation. Data gathered in this qualitative research suggest that regular quality inclusive HPE lessons increased students potential for spiritual experiences.